Impact of institutional forces and availability of slack on corporate environmental behavior: Evidence from a developing country - Farida Saleem; Chinnam Gopinath (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
In this study we evaluate the corporate environmental activities within the framework of institutional forces, availability of slack and "taking a developing country as the field of study. This paper integrates the institutional approach and slack resource theory to develop a model and then tests this model in a developing country context. Data were collected through a questionnaire survey from managers operating in a variety of industries in Pakistan. Stepwise Hierarchical linear regression was used for analysis. Media concern and discretionary slake were presented as moderator of purposed relationships. The results validate previous findings from both developed and developing countries. This study makes an important contribution by identifying institutional pressures in the form of regulatory forces (coercive pressures), issue legitimation (normative pressures) and competitor concern (mimic pressures) as important drivers for corporate environmental strategies for Pakistani organizations. Similarly both media concern and discretionary slake also identified as moderators for all purposed relationships.
Keywords: 330; institutional approach; slack resource theory; developing country; corporate environmental activities